Silicon crystal strength reduction due to magnetoresonance - Makara, V.A.; Pogorilyi, A.M.; Steblenko, L.P.; Kuryliuk, A.M.; Naumenko, S.M.; Kobzar, Yu.L.; Kravets, A.F.; Podyalovsky, D.I.; Matveeva, O.V. (Functional Materials, 2007)
The magnetoresonance influence as well as the micrawave superhigh-frequency (SHF) magnetic field effect on the microhardness of silicon crystals has been studied. It is established that the action of SHF field results in decreasing microhardness, which does not relax for initial value during a long time (50 days). A mechanism has been suggested for the revealed effects.